Human neuraminidases have reduced activity towards modified sialic acids on glycoproteins. (November 2020) - Hunter, Carmanah D.; Porter, Elizabeth M.; Cairo, Christopher W.
Abstract: Multiple levels of diversity in sialic acid presentation can influence the substrate activity of sialosides for glycoside hydrolases. Few reports have investigated the specificity of human neuraminidase (hNEU) activity towards modified sialic acid residues that can occur on glycoproteins. Previously, we evaluated hNEU activity towards 9- O -acetylated sialic acid in glycolipid substrates and found that hNEU generally discriminated against 9- O -acetylated sialic acid over Neu5Ac. Here, we have investigated the substrate specificity of hNEU enzymes for a glycoprotein substrate (bovine submaxillary mucin) containing 9- O -acetylated and Neu5Gc residues. Using this model substrate, we observe a general trend for hNEU tolerance of Neu5Ac > Neu5Gc ≫ Neu5, 9Ac2, consistent with our previous results with glycolipid substrates. These results expand our understanding of hNEU enzyme specificity and suggest that naturally occurring modifications of sialic acids can play a role in regulating hNEU activity. Graphical abstract: Image 1 Highlights: Human NEU activity on glycoprotein substrates varies for unusual sialosides. NEU enzymes hydrolyze with a preference that follows: Neu5Ac > Neu5Gc ≫ Neu5, 9Ac2 . Preference of human NEU is compared to C. perfringens and A. ureafaciens sialidase. First determination of NEU1 preference for Neu5Ac over Neu5, 9Ac2 .